Incorporating Multicultural Literature in EFL Classroom - Vidya Mandarani; Ahmad Munir (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Nowadays’ multicultural education poses various challenges. One of the latent issues currently emerged in Indonesia education is the mistreatment towards the students of minority ethnic amongst the fellow learners. This status quo pushes schools’ stakeholders to reflect upon their responsibilities and reconsider the use of multiculturalism in enhancing diversity awareness towards both teachers and students. In an attempt to promote multicultural education, the use of multicultural literature that portrays various cultures, values, and views, may assist the students in appreciating their own culture by the acquisition of diverse perspectives of the society. Moreover, it provides potential teachers to comprehend the diversity of multicultural issues beyond mono-cultural perspectives. This paper aims to emphasize the significance of multicultural literature as teaching materials; recommend selection and evaluation criteria for the said literature; as well as to present strategies of formulating literature-based classrooms. In providing the best teaching materials, it is necessary to select high-quality multicultural literature to present accurate and authentic representations of cultural communities. At any rate, 10 overall criteria should be embedded within the selected literature, thus the QUILT metric can be utilized to assess its quality. Afterward, there are also several recommended approaches, techniques, or strategies for formulating a literature-based classroom that may promote critical thinking in literary discussion.